The (110) and (320) surfaces of a Cantor alloy. (1st May 2021) - Ledieu, J.; Feuerbacher, M.; Thomas, C.; de Weerd, M.-C.; Šturm, S.; Podlogar, M.; Ghanbaja, J.; Migot, S.; Sicot, M.; Fournée, V.
Graphical abstract: Abstract: The (110) and (320) surfaces of the single-phase FeCrMnNiCo solid solution have been studied on two adjacent millimeter size grains using surface science and transmission electron microscopy (TEM) techniques. The structural and chemical evolutions of the high entropy alloy (HEA) surfaces have been determined for various sputtering conditions, annealing temperatures and durations. Up to 873 K, angle-resolved X-ray photoelectron spectroscopy measurements indicate a clear Mn and Ni surface co-segregation. We propose that the surface segregation of Mn is driven by its low surface energy. The attractive interaction between Mn and Ni promotes Ni segregation which accompanied the Mn diffusion to the surface. Regarding the structures investigated by low energy electron diffraction and scanning tunneling microscopy, the (320) surface presents a terraced morphology with an ordered structure consistent with a ( 1 × 1 ) termination. On the contrary, the (110) surface reveals an important degree of structural disorder and local reconstructions. Its highly anisotropic morphology resembles rows propagating along the [001] direction. Above 873 K, Mn desorption occurs while the Ni content keeps increasing linearly with the temperature. TEM analysis show no evidence for HEA decomposition into metallic or intermetallic phases even after repeated annealing and sputtering cycles. The above results set the upper temperature limit above which the surface stoichiometry departs from the quinary HEA concept. It also defines the temperature range for the use of FeCrMnNiCo based coating under high vacuum conditions and for aerospace applications.